Rol de la altura en el desarrollo de eritrocitosis aislada postrasplante renal: reporte de caso - Contreras Tovar, Angie Romina (2025)
Post-transplant erythrocytosis (PTE) is a hematological complication occurring in approximately 10-15% of kidney transplant recipients, characterized by persistent elevation of hemoglobin and hematocrit. Residence at high altitude may constitute an additional, underexplored risk factor. We report the case of a 44-year-old male, a resident of Huancayo (3,200 meters above sea level), with stage 5 chronic kidney disease secondary to hypertensive nephropathy, on hemodialysis for 3 years, who received a living-related donor kidney transplant. Two months post-transplant, he presented with headache, distal cyanosis, and general malaise, with persistently elevated hemoglobin (19.9-22.0 g/ dL) on serial measurements. Evaluation excluded other secondary causes of erythrocytosis. Treatment with acetylsalicylic acid 100 mg/day and phlebotomy resulted in clinical and analytical improvement. In conclusion, PTE is a multifactorial entity where high altitude may act as an additional predisposing factor through mechanisms of adaptation to chronic hypobaric hypoxia. Diagnosis requires serial measurements and altitude-adjusted reference values, and management should be individualized, considering the patient's geographical context.